The Identity of High-Achieving IT Professionals at Work: A Narrative Analysis - Taylor, Adam Peter Roy (Auckland University of Technology, 2010)
Self-identity has emerged from being a static function of essentialist categories like age, gender, race, and occupation, to being viewed as an interwoven and complex personalised construction based on a person’s environment, life experiences and interactions with others. This thesis adopts a perspective on self-identity as socially constructed and performed in encounters with others. In particular, identity is considered to be narrated to ourselves and to others. Self-identity is thus continually maintained and reworked in a search for ontological security as their context and their interaction with others changes. The value placed on highly skilled, expert labour in the new economy suggests that an examination of IT professionals’ identity construction in this context may have important implications. Accordingly, this study investigates the identity of ‘high-achieving IT professional’, and how these individuals narratively construct their identity in the context of their work. Extended narratives about work and career were collected from nine IT professionals considered to be ‘high-achieving’ by their peers and colleagues. All participants were interviewed in their place of work. Three of the participants were still operating in the technical realm, two had moved on to managerial roles, and four had moved on to executive or entrepreneurial roles in the IT industry. The narratives solicited from the participants were analysed using narrative based inquiry (Riessman, 1993). An inductive process produced a range of themes surrounding their identity work in the performance of self in the interview context. Examination of these themes suggests that the participants were drawing on and mobilising a range of individual identity capital ‘assets’ in order to negotiate a stable and secure sense of self in relation to their work and career. Their individual identity capital assets were derived from a number of generally available ‘sources of identification’, such as social and technical skills, occupational roles and relations, education, and behavioural repertoires. The narrative data analysis, in conjunction with consideration of relevant identity theory, particularly Cote’s (1996) notion of ‘identity capital’, led to the development of an analytical model of identity construction that was used to inform the presentation of the analysis. This model conceptualises identity work as the work individuals do in mobilising and drawing upon individual identity assets that comprise their identity capital, in turn derived and accrued from general and essentialist sources of identity, in order to perform their preferred selves in various contexts and interactions. The model is premised on the link between environment and identity, and therefore subscribes to an interpretation of identity as socially and narratively constructed in context. It demonstrates the socialising influence of institutions and their cultures, and the developments of individual resources or assets for identity construction. An analysis across all nine participant narratives identified a range of commonalities in how these high-achieving IT professional’s identity construction. These commonalities include the use of skills and experience in constructing their sense of self, the importance of education (or its lack) in framing identity, and a keen focus on relationships that appears counter to the prevailing technological stereotype. They continued to use hierarchy and a mechanistic metaphor as a means of placing themselves in relation to their world, to identify with role and not the employer, and to use of aspects of the new economy such as the commodification of knowledge and skills, in constructing an ontologically secure sense of self. Based on these and other common elements in the participants’ narrative construction of identity, the potential for an archetypical ‘high-achieving IT professional’ is discussed.
Keywords: Identity; IT Professionals; High-achieving; Work; Narrative; Constructed identity; Self; Commonalities; Capital; Assets